Insufflation with carbon dioxide reduces pneumoperitoneum after percutaneous endoscopic gastrostomy (PEG): a randomized controlled trial - Murphy, Christopher J.; Adler, Douglas G.; Cox, Kristen; Sommers, Daniel N.; Fang, John C. (Endoscopy International Open, 2016)
Background and study aims: Pneumoperitoneum following PEG placement has been reported in up to 60 % of cases, and while usually benign and self-limited, it can lead to evaluation for suspected perforation. This study was designed to determine whether using CO2 compared to ambient air for insufflation during PEG reduces post-procedure pneumoperitoneum. Patients and Methods: Prospective, double-blind, randomized trial of 35 consecutive patients undergoing PEG at a single academic medical center. Patients were randomized to insufflation with CO2 or ambient air. The primary outcome was pneumoperitoneum determined by left-lateral decubitus abdominal x-rays 30 minutes after PEG placement. Secondary endpoints included abdominal distention, pain, and bloating.Results: PEG was successfully placed in 17 patients using CO2 and 18 patients using ambient air. Three patients in each arm were unable or declined to have x-rays completed and were excluded. Pneumoperitoneum was identified in 2/14 (14.3 %) using CO2 and 8/15 (53.3 %) using ambient air (P = 0.05). There was no significant difference in abdominal distention, visual analog scale (VAS) scores for pain or bloating between CO2 and ambient air. Conclusion: Utilizing CO2 significantly reduces the frequency of post-procedural pneumoperitoneum compared to use of ambient air during PEG placement, with no difference in waist circumference, pain or bloating between CO2 and ambient air. CO2 appears to be safe and effective for use and may be the insufflation agent of choice during PEG.